2013
DOI: 10.1371/journal.pone.0069100
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pre-Attentive Arousal in Young Children with Autism Spectrum Disorder Contributes to Their Atypical Auditory Behavior: An ERP Study

Abstract: Auditory sensory modulation difficulties and problems with automatic re-orienting to sound are well documented in autism spectrum disorders (ASD). Abnormal preattentive arousal processes may contribute to these deficits. In this study, we investigated components of the cortical auditory evoked potential (CAEP) reflecting preattentive arousal in children with ASD and typically developing (TD) children aged 3-8 years. Pairs of clicks (‘S1’ and ‘S2’) separated by a 1 sec S1-S2 interstimulus interval (ISI) and muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 133 publications
(199 reference statements)
4
47
0
4
Order By: Relevance
“…Decreased amplitude of the P1 peak at fronto-central electrodes has been described using both a classical P1 suppression paradigm in children aged 7–12 years with Asperger’s syndrome (Madsen et al, 2015) and in children aged 7–12 years with ASD by presenting speech and non-speech sounds (Lepisto et al, 2005). This latter finding was replicated in a more recent study which reported decreased amplitude of a later component of the P1 in the central region in children aged 3–8 years with ASD (Stroganova et al, 2013). Increased variability of P1 amplitude and latency between trials may also occur in individuals with ASD (Milne, 2011).…”
Section: Sensory Processing In Individuals With Asd and Fxssupporting
confidence: 56%
“…Decreased amplitude of the P1 peak at fronto-central electrodes has been described using both a classical P1 suppression paradigm in children aged 7–12 years with Asperger’s syndrome (Madsen et al, 2015) and in children aged 7–12 years with ASD by presenting speech and non-speech sounds (Lepisto et al, 2005). This latter finding was replicated in a more recent study which reported decreased amplitude of a later component of the P1 in the central region in children aged 3–8 years with ASD (Stroganova et al, 2013). Increased variability of P1 amplitude and latency between trials may also occur in individuals with ASD (Milne, 2011).…”
Section: Sensory Processing In Individuals With Asd and Fxssupporting
confidence: 56%
“…With regard to EEG, few studies have reported abnormal P1 components in children with ASD. 71,72 One previous study demonstrated shorter latencies of the P1 evoked by binaural tone stimuli (1 kHz) in children with ASD (eight boys, mean age 8.5 years old) than in typically developing (TD) children (nine boys, mean age 8.5 years old). 72 However, previous MEG studies have not reported a shorter latency of the P1m in children with ASD in either the right or left hemispheres, 7,26 and one recent MEG study demonstrated a longer latency in 6-10-year-old children with ASD in both the right and left hemispheres.…”
Section: Aef and Aep Studies In Children With Asdmentioning
confidence: 98%
“…Further stimulus‐specific and age‐specific studies on children with a wider age range will be crucial for gaining insight into the underlying neurophysiology of these developing and complex phenomena. With regard to EEG, few studies have reported abnormal P1 components in children with ASD . One previous study demonstrated shorter latencies of the P1 evoked by binaural tone stimuli (1 kHz) in children with ASD (eight boys, mean age 8.5 years old) than in typically developing (TD) children (nine boys, mean age 8.5 years old) .…”
Section: Aef and Aep Studies In Children With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, the N100 originates from activation of superficial supragranular layers of the cortex (Moore, 2002; Stroganova et al, 2013), the primary origin and termination of intracortical connections (Swenson, 2006). Thus, pathology affecting these layers and projections may reduce N100 responses.…”
Section: Introductionmentioning
confidence: 99%